KONSELING KELOMPOK DENGAN TEKNIK SELF CONTROL TERHADAP KECEMASAN BELAJAR SISWA - Saputri, Naning Eky; Subiyanto, Subiyanto; Indiati, Indiati (Universitas Muhammadiyah Magelang, 2014)
This study aimed to examine the effect of group counseling techniques of self-control in reducing the anxiety of student learning. The study was conducted on students of SMP N 12 City of Magelang. Design of this research is pre experiment with one group pretest posttest design. Samples taken as many as 10 incoming students in the experimental group, namely the group treated (group counseling techniques of self-control). The technique of sampling using purposive sampling. The technique of collecting data using questionnaires. The results showed students’ anxiety decreased after attending group counseling techniques of self-control. Decreased anxiety, learning siswaditunjukkan with a reduction in post test scores, the average score pre test which was originally 125.10 after a given treatment group counseling techniques of self-control showed a decrease in the average post-test score tmenjadi 104.50 with significant value 0.005. This is also evidenced by the change in student behavior. Students who originally did not have a responsibility to behavior which is often out of class at the turn of lesson hours and did not seriously follow the lessons after a given treatment group counseling techniques become more self control can control the behavior that is detrimental to him during the process of learning. Based on this it can be concluded that the self-control group counseling techniques to decrease anxiety affect student learning.